Roles and Responsibilities of a Notary in Drawing up a Deed of Amendment to the Articles of Association of a Limited Liability Company - Hariyanti, Agus Fitri; Purnawan, Amin (Jurnal Konstatering, 2022)
This study aims to analyze: 1) The role of a notary in making a notarial deed regarding for amending the articles of association of a limited liability company. 2) The responsibility of a notary in making a notarial deed regarding the procedure for amending the articles of association of a limited liability company. The approach method in this research is a sociological juridical approach. The research specifications used are analytical descriptive research. Types of data using primary data and secondary data. Data collection by interview method and literature study. The data analysis method used is qualitative analysis. The results of the study concluded: 1) The role of the notary in making a notarial deed regarding the procedure for amending the articles of association of a limited liability company, namely making an application for amending the articles of association electronically through SABH by completing supporting documents obtained from the General Meeting of Shareholders (GMS). The procedure for amending the articles of association must be carried out in accordance with the provisions in Act No. 40 of 2007 concerning Limited Liability Companies and Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 21 of 2021 concerning Requirements and Procedures for Registration of Establishment, Change and Dissolution of Limited Liability Company Legal Entities. 2). The responsibility of a notary in making a notarial deed regarding the procedure for amending the articles of association of a limited liability company is to be responsible for reporting to the Minister as stated in Article 10 Jo. Article 12 Permenkumham Number 21 of 2021. A Notary who is negligent or intentionally does not report changes to company data to the Minister and or does not submit related documents to appearers for the benefit of the PT, can cause harm to the PT so that the Notary concerned can be deemed to have committed an unlawful act and violated the code Notary ethics.